C1-C2 fusion: postoperative C2 nerve impingement—is it a problem? - Myers, Kurt D; Lindley, Emily M; Burger, Evalina L; Patel, Vikas V (Evidence-Based Spine-Care Journal, 2012)
Objective: The purpose of this comparison case study is to show a potential complication associated with atlantoaxial fusion, and the preoperative evaluation that could help to avoid it.Background data: The use of lateral mass screw fixation in atlantoaxial fusion has provided surgeons the ability to create rigid fixation, with a high success rate of fusion. While the use of screws for fixation is relatively easy to adopt, the risk of causing neurological damage to the patient is ever present. Many major structures, such as the vertebral artery, carotid artery, and spinal cord, must all be considered during surgery.Methods: A comparison of two patients who underwent the same procedure was reviewed—the first had no complications from surgery and the second underwent revision surgery because of the C1 screw impinging on the C1 nerve exiting the foramen.Results: After removal of the C1 screw and converting to a cable technique, the patient made a full recovery and neurological function was restored.Conclusions: When considering C1-C2 lateral mass screw fixation for atlantoaxial fusion, the size of the foramen should be considered. If the foramen is significantly narrowed, alternate fixation should be selected.